2013
DOI: 10.1007/s12033-013-9680-6
|View full text |Cite
|
Sign up to set email alerts
|

The Rep20 Replication Initiator From the pAG20 Plasmid of Acetobacter aceti

Abstract: In the previously isolated pAG20 plasmid from the Acetobacter aceti CCM3610 strain, the Rep20 protein was characterized as a main replication initiator. The pAG20 plasmid origin was localized in the vicinity of the rep20 gene and contained two 21-nucleotide-long iteron sequences, two 13-nucleotide-long direct repeats, and a DnaA-binding site. Electrophoretic mobility shift assay and nonradioactive fragment analysis confirmed that the Rep20 protein interacted with two direct repeats (5'-TCCAAATTTGGAT'-3') and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…2010 ). Although ISSR methods offer a relatively easy and inexpensive access to molecular genetic study ( Cichorz et al . 2014 ), yet several researchers doubts about their reproducibility, ascendancy, and homology ( Hansen et al .…”
Section: Discussionmentioning
confidence: 99%
“…2010 ). Although ISSR methods offer a relatively easy and inexpensive access to molecular genetic study ( Cichorz et al . 2014 ), yet several researchers doubts about their reproducibility, ascendancy, and homology ( Hansen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a well-defined method for the classification of Acetobacter plasmids has not been developed. Two groups have recently reported the characterization of Rep proteins, Rep7 and Rep20, from small plasmids pGR7 (Grones and Grones, 2012 ) and pAG20 (Babic et al, 2014 ), respectively, found in Acetobacter (class Rhodospirillales ). The Rep20 gene was also found in plasmids in Rhodospirillales and Rhodobacteriales (Figure 3C ).…”
Section: Plasmids In Alphaproteobacteriamentioning
confidence: 99%
“…Previous studies have shown that harpin, applied as a foliar spray or expressed in plants, confers resistance to pathogens 14 24 45 46 . The antimicrobial proteins, cecropin A-melittin, also effectively confer plants with a resistance to a broad spectrum of pathogens 33 34 35 . Resistance to tobacco mosaic virus, bacterial Ralstonia solanacearum , and fungal Magnaporthe oryzae infections can be improved by spraying Hcm1 protein on plants prior to inoculation with plant pathogens 22 .…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the spread of V. dahliae was effectively hindered. A synthetic chimera of cecropin A and melittin CAPs with antimicrobial properties, MsrA1, effectively restricts Alternaria brassicae and Sclerotinia sclerotiorum infection in transgenic Brassica juncea and Solanum tuberosum plants 34 56 . The novel cecropin A-melittin hybrid peptide, CEMA, which has strong antimicrobial activity in vitro , confers resistance against Fusarium solani in transgenic tobacco 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation